anonymous
  • anonymous
Help !!! Write an equation of a line that passes through the point (3, 2) and is parallel to the line y = 3x - 4 y = 3x + 7 y = 3x - 7 y =1/3 x + 2 y =1/3 x - 2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Use the point slop form and then convert it to y-intercep form
anonymous
  • anonymous
so y=mx+b . but i dont know which letters go with the numbers
anonymous
  • anonymous
Point slope form = \( \huge y – y_1 = m(x – x_1)\) Put the point (3, 2) into that equation. \( \huge y – y_1 = m(x – x_1)\) \( \huge y – 2 = m(x – 3)\) Since we know it is going to be parallel, we know that it is going to have the same slope of y = 3x - 4. The slope is 3 so we have \( \huge y – 2 = 3(x – 3)\) Now transfor this \( \huge y – 2 = 3(x – 3)\) into y-intercept form y = mx + b Can you finish ?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
y-2= 3x+-3?? Im sorry im so confused
anonymous
  • anonymous
You are on the right track. \( \huge y – 2 = 3(x – 3)\) Now distribute the 3 in the () \( \huge y – 2 = 3(x – 3)\) \( \huge y -2 = 3x - 9\) Now add 2 to each side of the equation. \( \huge y -2 + 2 = 3x -9 + 2 \) Can you finish?.
anonymous
  • anonymous
y=3x-7
anonymous
  • anonymous
Correct!!!
anonymous
  • anonymous
Good job
anonymous
  • anonymous
So B
anonymous
  • anonymous
Yep!!!
anonymous
  • anonymous
Thank you soo much for helping me and being so patient
anonymous
  • anonymous
Anytime!!! That is what I am here for :-D
anonymous
  • anonymous
Thank you for learning and working hard!!!
anonymous
  • anonymous
Only thanks to you

Looking for something else?

Not the answer you are looking for? Search for more explanations.